Tax Planning atas Pajak Penghasilan Badan pada PT Unilever Indonesia, Tbk Tahun 2023 dan 2022 - Novi Purnamasari; Fadhilah Rasyid Hafifi; Praba Sita; Dian Indah Sari (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to investigate in detail the tax planning and implementation strategies applied by PT Unilever Indonesia Tbk in fulfilling its Corporate Income Tax (CIT) obligations. While taxes serve as a major source of government revenue, they also represent a financial burden for businesses that can impact net profits. Therefore, the implementation of a carefully designed tax planning approach is crucial to effectively manage tax liabilities while remaining compliant with existing legal regulations. The research employs a descriptive-analytical method, supported by a review of relevant literature and the use of secondary data obtained from taxation-related documentation. The study seeks to identify the tax planning protocols adopted by the company and assess their influence on the effectiveness of the firm’s tax-related financial expenditures. The findings reveal that PT Unilever Indonesia Tbk has successfully implemented tax planning strategies through the strategic utilization of deductible expenses as outlined in Article 6(1) of the Indonesian Income Tax Law, which includes expenditures for employee training, research and development activities, and corporate social responsibility (CSR) initiatives. This approach allows the company to legally reduce its tax obligations while enhancing its financial efficiency. The insights gained from this research are expected to serve as a framework for other organizations in developing tax planning policies that are not only effective and efficient but also sustainable in the long term.